Neuro-Ophthalmology - Somlai, Judit; Kovács, Tibor (Springer International Publishing : Imprint: Springer, 2016)
This practical guide provides a complete algorithm for diagnosis and treatment, from 'having a problem with vision', via background and diagnosis, to treatment and eventually to rehabilitation of visual loss and eye-movement disorders in the central nervous system. Following on from introductory sections devoted to the role of neuro-ophthalmology, recent developments in the field, and an overview of neuro-ophthalmological examinations, there are sections devoted to the different parts of the visual system, and finally a section on rehabilitation. The handbook gives an overall picture for all interested in neuro-ophthalmology, borderline territories and overlaps. Neuro-Ophthalmology is aimed at ophthalmologists, neurologists, neurosurgeons, traumatologists, neuroradiologists, experts in cardiology and stroke, and trainees in these areas. It will also be of interest to neuro-rehabilitation specialists, neuropsychologists, and those working in typhlopedagogy and health informatics.